Demystifying the results obtained through the use of SGLT-2 inhibitor drugs, used by patients at the Reference Center for Hypertension and Diabetes Rio Verde - Goiás (Research, Society and Development, 2023)
Introduction: Due to the increase in glucose excretion of renal sodium-glucose cotransporter 2 (ISGLT-2) inhibitors, there is also a reduction in weight through its glycosuric effect. Objective: To analyze the efficacy of ISGLT-2 based on medical records and glycemic levels according to glycated blood glucose; to verify which medications are most prescribed and to observe poor adherence due to side effects in patients of the CRHD in Rio Verde-GO. Methods: A descriptive observational study was carried out using the medical records of diabetic patients treated at the CRHD as the main means of data collection, identifying and comparing laboratory values based on the different pharmacological conducts performed. And manually organize and group the search results on the Excel platform, where they will later be converted into easy-to-view graphs for the public. Results And Discussion: When analyzing the glycated hemoglobin (HbA1c) of the patients before and after the introduction of the ISGLT-2 class, it was noted that 80% obtained a laboratory improvement and 20% a worsening. The results reveal that 80% had an improvement in glycated hemoglobin, as they presented good adherence to the medication and specific and balanced nutrition for their condition. Conclusion: There is an improvement in glycated hemoglobin in most of the patients treated at the CRHD who are users of iSGLT-2, where the most used medication is Forxiga (Dapaglifozin), which is part of the medications of the SUS network.